2018
DOI: 10.1371/journal.pone.0197580
|View full text |Cite
|
Sign up to set email alerts
|

Should kissing balloon inflation after main vessel stenting be routine in the one-stent approach? A systematic review and meta-analysis of randomized trials

Abstract: The KBI (kissing balloon inflation) technique is considered the default strategy for the two-stent approach in real world practice. Studies comparing KBI and No-KBI in patients undergoing the one-stent approach have reported conflicting results. The meta-analysis was performed to compare the clinical outcomes of the KBI strategy and the No-KBI strategy for coronary bifurcation lesions in the one-stent approach. Five randomized studies were included, and a total of 1264 patients were involved in the meta-analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 23 publications
0
23
0
1
Order By: Relevance
“…In the latest meta-analysis of five randomized studies of KBI, although the KBI strategy reduced the incidence of side branch restenosis, there was no significant difference in clinical outcomes such as cardiac death, myocardial infarction, stent thrombosis, target lesion revascularization (TLR), and target vessel revascularization (TVR) between the KBI strategy and a no-KBI strategy for coronary bifurcation lesions in the one-stent approach [18]. However, the optimal rewiring afforded by a 3D reconstruction system with high diagnostic performance might be able to change the results of bifurcation PCIs.…”
Section: Discussionmentioning
confidence: 99%
“…In the latest meta-analysis of five randomized studies of KBI, although the KBI strategy reduced the incidence of side branch restenosis, there was no significant difference in clinical outcomes such as cardiac death, myocardial infarction, stent thrombosis, target lesion revascularization (TLR), and target vessel revascularization (TVR) between the KBI strategy and a no-KBI strategy for coronary bifurcation lesions in the one-stent approach [18]. However, the optimal rewiring afforded by a 3D reconstruction system with high diagnostic performance might be able to change the results of bifurcation PCIs.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, the PS protocol differed between the two studies—in EBC MAIN kissing balloon inflation (KBI) of the side vessel after stenting was a part of the procedure, whereas in DKCRUSH-V KBI was permitted only if residual DS of the side branch was >75%, or dissection ≥ type B, or Thrombolysis In Myocardial Infarction (TIMI) flow grade < 3 was present. As the studies comparing KBI with no-KBI in a one-stent approach provide non-consistent results, this difference in protocols presumably influenced the final outcomes of the aforementioned RCTs [ 119 ]. Lastly, it is noteworthy that operators included in the DKCRUSH-V study had to be well-experienced, as it was confirmed by sending three to five cases to the trial steering committee, which to some extent might have driven favorable DK crush outcomes.…”
Section: Percutaneous Management Techniquesmentioning
confidence: 99%
“…In a recent meta-analysis, routine final KBI resulted in a significant reduction in SB restenosis, but an increase in MV restenosis rates with no significant differences in clinical outcomes[ 73 ]. Another recent larger meta-analysis of final KBI vs no-final KBI in PST trials also showed similar results in that there was no difference in terms of MACEs and other outcomes[ 74 ].…”
Section: Pstmentioning
confidence: 99%